1993
DOI: 10.1063/1.860652
|View full text |Cite
|
Sign up to set email alerts
|

Wave collapse at the lower-hybrid resonance

Abstract: The modulational instability and collapse of waves in the vicinity of the lower-hybrid resonance including both magnetosonic and lower-hybrid waves are investigated by analytical and numerical methods. The mechanism leading to the modulational instability is the nonlinear coupling of lower-hybrid waves with the much lower-frequency quasineutral density perturbations via the ponderomotive force. The result is a filamentation of the high-frequency field producing elongated, cigar-shaped nonlinear wave packets al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 10 publications
5
76
1
Order By: Relevance
“…In this case the result for δn~ (E × E * ) z coincides with that found in Ref. [7]. The sign of δn is not determined.…”
Section: Electron Density Perturbationssupporting
confidence: 76%
“…In this case the result for δn~ (E × E * ) z coincides with that found in Ref. [7]. The sign of δn is not determined.…”
Section: Electron Density Perturbationssupporting
confidence: 76%
“…We calculated estimates of threshold wave amplitudes for the modulational instability [e.g., Shapiro et al, 1993] and then converted the electric field amplitudes to magnetic field amplitudes [e.g., Huba et al, 1978]. We find that 10/11 of the MIXED modes satisfy the threshold criteria for the modulational instability.…”
Section: Interpretation Of Wave Modesmentioning
confidence: 99%
“…In the case of large-amplitude LFWs, strong lower hybrid (LH) turbulence could be produced Khazanov et al, 1996]. Strong LH turbulence results in plasma heating and acceleration [Shapiro et al, 1993], the formation of ion conics [Chang and Coppi, 1981;Retterer et al, 1986], and possibly the saturation of Alfv6n oscillations in the ring current region . Weak LH turbulence can also lead to important changes in the plasma state; for example, Ornelchenko et al [1994] found that the LH "fan" instability may accelerate ions.…”
Section: Description Of the Problemmentioning
confidence: 99%